Desain Media Google Earth untuk Pembelajaran Geografi SMA Kelas X Materi Dinamika Hidrosfer - Nurhaydah, Nurhaydah; Maryati, Sri; Lahay, Rakhmat Jaya (Universitas Negeri Gorontalo, 2025)
This study explores the design process of instructional media using Google Earth to support senior high school Geography learning on Hydrosphere Dynamics. The media was developed through a location-based approach that integrates satellite imagery, placemarks, interactive maps, and visual narration to present content in a contextual and exploratory way. The design process is aligned with the Merdeka Curriculum, structured around learning objectives, strategic location selection, and multimedia element integration. A storyboard was used to ensure continuity between visual and narrative components, allowing for a coherent and meaningful learning flow. The development demonstrates that geospatial-based learning media can foster relevant, engaging, and participatory educational experiences. This study is limited to the design phase; therefore, future research is needed to assess its effectiveness in enhancing student learning outcomes through classroom implementation.